The Late Medieval Origins of the Modern Novel - Kent, Rachel A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Dramatically refreshing the age-old debate about the novel's origins and purpose, Kent traces the origin of the modern novel to a late medieval fascination with the wounded, and often eroticized, body of Christ. A wide range of texts help to illustrate this discovery, ranging from medieval 'Pietàs' to Thomas Hardy to contemporary literary theory.
Keywords: Literature; Literature -- History and criticism; Literature, Modern; Literature, Medieval; Fiction; European literature; British literature; Literature; Medieval Literature; British and Irish Literature; Early Modern/Renaissance Literature; Fiction; Literary History; European Literature; Electronic books